Determining the Direction of the Pesantren (Empowering Leadership Practice at PM Gontor 6 Putera, Southeast Sulawesi) - Suryadi Suryadi; Syahrul Syahrul (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
This article aims to understand the practice of empowering leadership, which is more specific on the theme of determining the direction of pesantren. The aspects studied are: 1) creating a vision; 2) describes the big picture; and 3) establishing a strategy. The investigation was carried out in the form of critical ethnography, where data were obtained through a process of observation, interviews, and document review. Data analysis was carried out through the description, analysis, and interpretation stages. This study found that: Empowering Leadership in the context of determining the direction of the organization at PM Gontor 7 Putera is a process of determining the vision and mission, explaining the big picture, and setting strategy. The roles carried out include being a strategic architect who defines PM Gontor's vision and mission, through internal and external environmental analysis, guarding a shared vision, overseeing the process of achieving a common vision at the functional level, as a figure who transforms strategy, who carries out the strategic communication process and makes appropriate measures, aligning strategies, to implementation. This research suggests the importance of building empowering leadership, having a strong vision, understanding internal and external dynamics, all of which can be formulated in an organizational strategy.Keywords: Leadership, Empowerment, Vision, Strategy